Jurilinguistique et lexicographie. Une première canadienne : le Dictionnaire de droit privé - Gémar, Jean-Claude (Les Cahiers de droit, 1986)
For historic reasons — legal traditions, language issues and lawyers' inhibitions — there has never been an authoritative, monolingual French legal dictionary in Canada. Since the publication in 1985 of the first edition of the Dictionnaire de droit privé by the Quebec Research Centre on Private and Comparative Law, this gap is now being filled. The interdisciplinary team engaged in this far-reaching lexicographic project is comprised of both legal and linguistic experts. Problems arising from the interaction of the French and English legal traditions in Canada are discussed. This paper outlines the principles and methods involved, derived primarily from a Canadian-based jurilinguistics, and the uses to which they are put.